"Mummy, keep it steady": phonetic variation shapes word learning at 15 and 17 months. Issue 5 (29th December 2017) - Escudero, Paola; Mulak, Karen E.; Elvin, Jaydene; Traynor, Nicole M.
Abstract: Fifteen‐month‐olds have difficulty detecting differences between novel words differing in a single vowel. Previous work showed that Australian English (AusE) infants habituated to the word‐object pair DEET detected an auditory switch to DIT and DOOT in Canadian English (CanE) but not in their native AusE (Escudero et al., 2014 ). The authors speculated that this may be because the vowel inherent spectral change variation (VISC) in AusE DEET is larger than in CanE DEET. We investigated whether VISC leads to difficulty in encoding phonetic detail during early word learning, and whether this difficulty dissipates with age. In Experiment 1, we familiarized AusE‐learning 15‐month‐olds to AusE DIT, which contains smaller VISC than AusE DEET. Unlike infants familiarized with AusE DEET (Escudero et al., 2014 ), infants detected a switch to DEET and DOOT. In Experiment 2, we familiarized AusE‐learning 17‐month‐olds to AusE DEET. This time, infants detected a switch to DOOT, and marginally detected a switch to DIT. Our acoustic analysis showed that AusE DEET and DOOT are differentiated by the second vowel formant, while DEET and DIT can only be distinguished by their changing dynamic properties throughout the vowel trajectory. Thus, by 17 months, AusE infants can encode highly dynamic acoustic properties, enabling them to learn the novel vowel minimal pairs that are difficult at 15 months. These findings suggest that the development of word learning is shaped by the phonetic properties of the specific word minimal pair. Abstract : We demonstrate that learning of novel words that differ in a single vowel can occur at 15 months depending on the acoustic properties of the vowel contrast that distinguishes the words. Contrasts involving dynamic properties are more challenging even at 17 months of age. Our findings have implications for theories of lexical and phonological development.